Peranan Kompetensi Guru MTs As-Adiyah Atapange Kec. Majauleng Kab. Wajo dalam Meningkatkan Minat Belajar Siswa - Tanawali, Besse (JURNAL AL-QAYYIMAH, 2019)
This article discusses the role of teacher personality competency in MTs As'adiyah Atapange of Majauleng Kab district. Wajo. This research uses quantitative data analysis, then the results showed that by using the formula Poduct moment obtained 0.233 was consulted with product moment or n = 1 at a significant level 5% = 0.116 and at a significant level 1% = 0 , 180, it turns out the value [R] is above the [r] Table product moment so the proposed hypothesis is received. Thus there is a  positive influence among the teacher's personality competencies towards student learning interests. Then the personality competence that teachers have is able to increase the spirit of learning, so that students have a study interest in students at MTs As'adiyah Atapange Kec. Majauleng Kab. Wajo.